(untitled) (REGE Revista de Gestão, 2023)
Purpose: Identify the scale efficiency of dry ports in Brazil and its main technological drivers. Design/methodology/approach: This paper uses the Data Envelopment Analysis (DEA) model in two stages. The first stage of the DEA was used to measure the efficiency of the dry ports. In the second stage, the Bootstrap Truncated Regression (BTR) was applied to explore the relationship between efficiency and the factors analyzed. The inputs, outputs, and contextual variables for this analysis were extracted from the secondary database provided by Revista Tecnologística. Findings: In the first analysis stage, a high level of idleness was verified in the operations. The contextual variables in the second stage were significant: Certification, Warehouse Management System (WMS), Barcode, and Radio Frequency Identification (RFID). Results corroborate the positive impact of Information Technology (IT) coordination processes on logistics performance. Practical Implications: Results show that dry ports operate below their technical and operational capacity and that the sector's lack of regulation in Brazil can facilitate and encourage the use of ports and marine terminals by importers and exporters. Originality: Application of two-stage DEA measures efficiency as a sectoral benchmarking tool.